Conflict and Collisions in Sub-Saharan African Urban Definitions: Interpreting Recent Urbanization Data From Kenya. (September 2017) - Potts, Deborah
Highlights: Urban definitions need to be considered when urban trends are analyzed. Used alone, population density criteria can include rural populations as "urban". Analysis of Kenyan urbanization is hindered by problematic urban definitions. Migration flows may be obscured if many rural people are defined as urban. Policy-relevant analysis is improved if urban definitions include occupations. Summary: This paper explores the challenges for analysis of urbanization which can arise from insufficiently rigorous definition of what is "urban". Policy makers and investors still use the ideas of "rural" versus "urban" and increasingly assume that the pace of urbanization in African countries is a measure of positive economic structural change. However most urban definitions do not incorporate economic characteristics. In Africa widely differing urban population thresholds and administrative factors are the most common criteria. The thresholds are often so low that many rural settlements are also defined as "urban" or they may be included on population density criteria, meaning the apparent pace of urbanization is inflated unrealistically. These issues are exemplified in this paper through detailed examples drawn from Kenya. It uses a range of sources including official census data and urban data published by Africapolis, as well as aerial images of rural and urban settlements in Kenya. It demonstrates how the use of population density criteria has inflated Kenyan urban data by the incorporation of very large numbers of rural people and explains how this can lead to entirely misleading interpretations of local and national urban and migration trends. Errors in urban figures can therefore have serious policy implications. It is argued that such errors can be reduced by not relying on a single criterion to define "urban" or by triangulating data on rural and urban settlements with other relevant information.